Severity of Disease in Humanized Mice Infected With Ebola Virus or Reston Virus Is Associated With Magnitude of Early Viral Replication in Liver. (26th October 2017) - Spengler, Jessica R; Saturday, Greg; Lavender, Kerry J; Martellaro, Cynthia; Keck, James G; Nichol, Stuart T; Spiropoulou, Christina F; Feldmann, Heinz; Prescott, Joseph
Abstract : Ebola virus, but not Reston virus, caused disease in NSG-SGM3 humanized mice, similar to infection in humans. Higher viral replication in liver and liver enzyme abnormalities in Ebola-infected mice suggest that organ-specific differences between ebolaviruses contribute to severity of disease. Abstract: Both Ebola virus (EBOV) and Reston virus (RESTV) cause disease in nonhuman primates, yet only EBOV causes disease in humans. To investigate differences in viral pathogenicity, humanized mice (hu-NSG-SGM3) were inoculated with EBOV or RESTV. Consistent with differences in disease in human infection, pronounced weight loss and markers of hepatic damage and disease were observed exclusively in EBOV-infected mice. These abnormalities were associated with significantly higher EBOV replication in the liver but not in the spleen, suggesting that in this model, efficiency of viral replication in select tissues early in infection may contribute to differences in viral pathogenicity.